Robotiziran montažni sistem kot sodelujoča večdelna organizacija - Jerbić, Bojan (Strojniški vestnik, 2003)
This paper looks at designing a robotic assembly system as a multi-agent system. Any multi-device system, or any system whose performance is naturally decomposable, can be interpreted as a corporation of agents. Sach a scheme comprises the ability to create a collaborative system that can provide the achieving of the social intelligence. Social behaviour is the highest form of intelligence, which is able to solve very complex problems, autonomously create new procedures and efficientlyadapt to new tasks. The presented multi-agent model is based on processing units that include recognition networks, problem-solving strategies and learning engines. It integrates perception, recognition, problem-solving, learning and communication capabilities. The reinforcement learning method is used here to evaluate the robot is behaviour and to induce new, or improve the existing, knowledge. The acquired action (task) plan is stored as experience, which can be used in solving similar problems in the future. To recognize problem similarities we applied the Adaptive Fuzzy Shadowed (AFS) neural network.
Keywords: montaža robotizirana; sistemi večdelni; členi neodvisni; metode učenja; mreže nevronalne; montažni sistemi; robotizacija; nevronske mreže